Strategi Integrating Brand Dan Nilai Komunikasi Produk Asuransi Syariah Dalam Meningkatkan Market Share - Irawan Fakhrudin Mahalizikri (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2016)
Lately turmoil insurance business began to squirm. The amount of reward for the insurance agent is one indication start growth and development of the insurance business. No exception is also rising cases of failure to pay an insurance company to the client. In Indonesia, there are two types of insurance, namely Takaful and conventional insurance. Venturing knowledge about Islamic insurance more easily since it will be life or animated about the background and origins of our clients. Development of insurance was not initially present but at that time still in a disguised form what namely that there is generally derived from human instincts who'd always tried to save themselves and the soul of a variety of threats, including the threat of malnutrition / pagan. Advances in technology and information as well as the majority of the population of our country Islam is a great opportunity and a vast market open for Takaful products and how the integration of brand and communication value in increasing market share.  Insurance history in Indonesia entered the Dutch colonial period is due to the success of the Dutch nation in the plantation sector and trade for the survival of their business, then the Dutch government made a very absolute and insurance business needed. Branch of insurance companies are in all of the colony with its head office in the Netherlands and English wear monopoly system in place so that the time was not yet known by the indigenous type of insurance that existed at the time of life and fire.